Antibody Binding and Angiotensin-Converting Enzyme 2 Binding Inhibition Is Significantly Reduced for Both the BA.1 and BA.2 Omicron Variants. (15th July 2022) - Junker, Daniel; Becker, Matthias; Wagner, Teresa R; Kaiser, Philipp D; Maier, Sandra; Grimm, Tanja M; Griesbaum, Johanna; Marsall, Patrick; Gruber, Jens; Traenkle, Bjoern; Heinzel, Constanze; Pinilla, Yudi T; et al.
Abstract: Background: The rapid emergence of the Omicron variant and its large number of mutations led to its classification as a variant of concern (VOC) by the World Health Organization. Subsequently, Omicron evolved into distinct sublineages (eg, BA.1 and BA.2), which currently represent the majority of global infections. Initial studies of the neutralizing response toward BA.1 in convalescent and vaccinated individuals showed a substantial reduction. Methods: We assessed antibody (immunoglobulin G [IgG]) binding, ACE2 (angiotensin-converting enzyme 2) binding inhibition, and IgG binding dynamics for the Omicron BA.1 and BA.2 variants compared to a panel of VOCs/variants of interest, in a large cohort (N = 352) of convalescent, vaccinated, and infected and subsequently vaccinated individuals. Results: While Omicron was capable of efficiently binding to ACE2, antibodies elicited by infection or immunization showed reduced binding capacities and ACE2 binding inhibition compared to wild type. Whereas BA.1 exhibited less IgG binding compared to BA.2, BA.2 showed reduced inhibition of ACE2 binding. Among vaccinated samples, antibody binding to Omicron only improved after administration of a third dose. Conclusions: Omicron BA.1 and BA.2 can still efficiently bind to ACE2, while vaccine/infection-derived antibodies can bind to Omicron. The extent of the mutations within both variants prevents a strong inhibitory binding response. As a result, both Omicron variants are able to evade control by preexisting antibodies. Abstract : Using a large diverse cohort of vaccinated and convalescent individuals, we found that Omicron can bind to angiotensin-converting enzyme 2 (ACE2) more efficiently than inhibitory antibodies. Immunoglobulin G binding and inhibition of ACE2 binding were significantly reduced for both BA.1 and BA.2.